Cloud technology : concepts, methodologies, tools, and applications - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This reference investigates the latest research in the ubiquitous Web, exploring the use of applications and software that make use of the Internet's anytime, anywhere availability"--Provided by publisher.
Fundamental concepts and theories -- Development and design methodologies -- Tools and technologies -- Utilization and application -- Organizational and social implications -- Managerial impact -- Critical issues -- Emerging trends.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 12/14/2014).
Keywords: Cloud computing; Web services; Big data analytics; Digital libraries; Enterprise 2.0; Identity management; Knowledge sharing; Security and privacy; Telemedicine; Web 2.0; Electronic books